The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1677/joe.0.1750143
|View full text |Cite
|
Sign up to set email alerts
|

IGF and IGF-binding protein expression in the growth plate of normal, dexamethasone-treated and human IGF-II transgenic mice

Abstract: Glucocorticoid (GC) treatment in childhood can lead to suppression of longitudinal growth as a side effect. The actions of GCs are thought to be mediated in part by impaired action of the insulin-like growth factors (IGF-I and IGF-II) and their binding proteins (IGFBP-1 to -6). We have studied the effects of GCs on IGF and IGFBP expression at the local level of the growth plate, using non-radioactive in situ hybridization.We treated 3-week-old normal mice for 4 weeks with dexamethasone (DXM). We also treated h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 55 publications
(90 reference statements)
3
27
0
Order By: Relevance
“…In addition, both Silvestrini et al (59) and Smink et al (60) reported that GC reduced growth cartilage width by inhibiting chondrocyte proliferation and increasing the apoptosis of terminal hypertrophic chondrocytes. Studies by our group and others have also shown that GCs impair chondrocyte proliferation and increase apoptosis (33,35,50,53,55,61). However, the mechanisms by which GCs exert control over chondrocyte dynamics are presently unclear.…”
mentioning
confidence: 94%
“…In addition, both Silvestrini et al (59) and Smink et al (60) reported that GC reduced growth cartilage width by inhibiting chondrocyte proliferation and increasing the apoptosis of terminal hypertrophic chondrocytes. Studies by our group and others have also shown that GCs impair chondrocyte proliferation and increase apoptosis (33,35,50,53,55,61). However, the mechanisms by which GCs exert control over chondrocyte dynamics are presently unclear.…”
mentioning
confidence: 94%
“…Furthermore, it is also not known whether IGF-I produced by different cell types within the bone (i.e., osteoblast, chondroblast, osteoclast, or marrow cells) exerts differential effects on longitudinal growth, bone width, and mineral deposition. In this regard, IGF-I produced by chondrocytes has been proposed to play a significant role in the regulation of longitudinal bone growth (33,47). This prediction is based on the findings that 1) chondrocytes both produce and respond to IGF-I (34,40), and 2) the rate of longitudinal growth is dependent on the rate of chondrocyte proliferation, as well as hypertrophic differentiation, which is accompanied by cell enlargement, which is disturbed in the IGF-I KO mice (49,50,53).…”
mentioning
confidence: 99%
“…In a previous study, we found upregulation of IGF-I expression in the growth plate of hIGF-II-transgenic mice in comparison with normal mice (Smink et al 2002). In addition, IGFBP-2 and -5 were increased in the spleen and thymus of these mice, whereas IGFBP-3 was increased exclusively in the spleen (Smink et al 1999).…”
Section: Introductionmentioning
confidence: 70%
“…The SV40 fragment detects only the mRNAs of the transgene as verified by Northern blot analysis (van Buul-Offers et al 1995). The use of both probes makes it possible to discriminate between endogenous and transgene IGF-II mRNAs (Smink et al 1999(Smink et al , 2002. Probes were checked for cross-hybridization, using in situ hybridization on different types of mouse tissues (spleen, thymus and whole embryos) for the IGFBP probes (Smink et al 1999, van Kleffens et al 2001; and on spleen and growth plate cartilage for the IGF probes (Smink et al 2002).…”
Section: Synthesis Of Digoxigenin-labeled Complementary Rna (Crna) Prmentioning
confidence: 99%